Ecolinguistics and Local Language Preservation: Children’s Folk Songs as a Tool for Revitalizing the Madurese Language - Sudarto Yoharwan Dwi; Khotimah Khusnul (SHS Web of Conferences)
This study aims to explore the role of tembang dolanan in the revitalization of the Madurese language through an ecolinguistic approach. Tembang dolanan, as part of local wisdom, not only serves as entertainment but also as an educational medium rich in cultural values, including Andhap Asor, which teaches humility and respect. Through an ecolinguistic analysis, this research reveals how tembang dolanan can function as an effective tool in preserving the Madurese language, which has experienced a decline in use among younger generations. The ecolinguistic approach allows this study to understand the interaction between language, culture, and the social environment in the Madurese context. The findings show that tembang dolanan not only helps in maintaining the language but also strengthens cultural identity and local values. The revitalization of the language through tembang dolanan is a strategic step in preserving linguistic and cultural diversity in Indonesia.